Utilization of Laparoscopic Wound Retractor for Extremely Low Birthweight Neonatal with Gastroschisis: Case Report and Literature Review - Fikri, Erjan; Fikri, Erjan; Alnaz, Ahmad Razi Maulana; Alnaz, Fini Meirisa (Journal of Neonatal Surgery, 2025)
Background : Gastroschisis is one of most devasting congenital anomaly. Cases in high-income countries are better due to early detection with early intrapartum interventions, somehow unable to apply in low-middle-income countries Case: Slightly preterm female neonate born with gastroschisis and extremely low birthweight at 1400gr in a primary care hospital. APGAR score of newborn was well, but due to limited resourced patient was transferred to referral hospital for pediatric surgery care. Patient then underwent emergency surgery, but bowel was matted and not reducible, so laparoscopic wound retractor was applied as alternative to Silastic Silo. Bowel was planned for staged reduction. Discussion: Staged reduction is one of considered treatment for gastroschisis. The application of silastic silo was no longer available, notably in low-middle income countries. This started an idea to modify the utilization of silo by using other sterile supplies which is possibly able to close. The use of the wound retractor was safe in contact to viscera and skin as commonly used for laparoscopy. Hence application in low-middle income countries was not yet much known. Conclusion: The utilization of wound retractor for temporary closure of gastroschisis can be considered whenever primary closure was not applicable and silastic silo was not available